The effect of grain orientation on secondary ion mass spectrometry (SIMS) analysis of rutile - Taylor, Rich; Clark, Chris; Reddy, Steven (Elsevier Science BV, 2012)
In situ high precision U–Pb analysis of rutile by secondary ion mass spectrometry (SIMS) reveals that instrumental bias for isotope ratios and count rates vary due to crystal orientation. Electron backscatter diffraction (EBSD) techniques have been combined with SIMS data to show consistent and systematic crystal orientation effects, whilst confirming that all analyses are on single crystals and that there is random variation from grain to grain. The result of the orientation effect is to produce an extremely large calibration slope, more than an order of magnitude larger than for other minerals, which can result in highly inaccurate and spurious U–Pb ages from rutile if not taken into account. We present a large standard dataset to highlight this effect and show that by collecting good standard data, from grains in multiple orientations, these effects can be negated and accurate U–Pb SIMS data for rutile can be obtained using a standard calibration slope of ln(Pb+/U+) vs ln(UO2+/UO+)=1.12. Examples from the Anantangiri region, Eastern Ghats, India are used to show the magnitude of these effects on the calibration of unknowns. Evidence is presented to show that the cause of these orientation effects is most likely a combination of channelling of primary ions into the crystal and preferential emission of secondary ions along preferred lattice directions.